High Accuracy Calculation of the Magnetic Vector Potential on Surfaces - Bibby, Malcolm M.; Peterson, Andrew F. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The calculation of integrals containing the free-space Green’s function in electromagnetic problems is difficult to perform with great accuracy. Three approaches to the calculation are investigated. The inadequacy of the singularity-subtraction method is demonstrated. The Duffy transform is shown to provide good results when the test-point is on the surface being investigated. A Maclaurin series expansion with integration prior to summation is shown to be efficient and reliable both on and off the surface under study. Solutions, in both Cartesian and cylindrical coordinate systems, that allow the calculations to be performed to a pre-defined level of accuracy are presented